VALUASI PENGENDALIAN EMISI BOILER BATU BARA PADA INDUSTRI KERTAS DAN ESTIMASI EMISI MERKURI (Hg) (VALUATION ON EMISSION CONTROL OF COAL-FIRED BOILER OF PAPER INDUSTRY AND ESTIMATION OF MERCURY (Hg) EMISSION) - Yusup Setiawan (Center for Pulp and Paper, 2017)
Steam and electricity needs in the paper industry have been provided itself through coal-fired boiler equipped with emission control devices. Boiler flue gas emissions of coal combustion products contain contaminants such as particulate emissions , NO2 and SO2 , and a small amount of emissions of mercury (Hg). Valuation on boiler emissions quality associated with air emissions control systems and emissions standard has been carried out. Estimation of mercury concentration in air emissions of boiler flue gas in the paper industry has also been conducted. The valuation on the air emissions quality of non-mercury parameters of paper industry boilers has also been done based on national emissions standards. The results of the valuation indicated that the current applied of flue gas emissions control devices in the paper industry has been optimally operated so that the emission quality of boiler for both non-mercury parameters and mercury parameters has been complied with the emission quality standards. Prediction of mercury content in air emissions of a coal boiler stack of paper industry that is discharged into environment based on the content of mercury in coal is 0.0205 mg/Nm3 (20.5 µg/Nm3 ) maximum. Paper industry needs to consider the application of co-benefit technology when mercury is used as a quality standard emissions parameter. ABSTRAKKebutuhan uap dan atau listrik pada industri kertas disediakan melalui unit boiler berbahan bakar batu bara yang dilengkapi alat pengendali emisi. Emisi gas boiler mengandung pencemar berupa partikulat, NO2 dan SO2 , dan merkuri (Hg). Valuasi kualitas emisi boiler berkaitan dengan sistem pengendalian emisi udara dan baku mutu emisi telah dilakukan, Estimasi kadar merkuri di udara emisi cerobong boiler pada industri kertas juga telah dilakukan. Valuasi kualitas emisi udara non-merkuri emisi boiler industri kertas juga telah dilakukan berdasarkan baku mutu emisi nasional. Hasil valuasi menunjukkan bahwa alat pengendali emisi gas buang boiler yang telah diterapkan saat ini pada industri kertas telah dioperasikan secara optimal sehingga kualitas emisi boiler baik untuk parameter non-merkuri maupun untuk parameter merkuri telah memenuhi baku mutu emisi. Prediksi kadar merkuri dalam udara emisi cerobong boiler batu bara industri kertas yang dibuang ke lingkungan dihitung berdasarkan kadar merkuri dalam batu bara adalah maksimum sebesar 0,0205 mg/Nm3 (20,5 µg/Nm3 ). Industri kertas perlu mempertimbangkan penerapan teknologi co-benefit bilamana suatu saat parameter merkuri ditetapkan sebagai parameter baku mutu emisi.